2014
DOI: 10.4081/ijas.2014.3154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yeast-Derived ProteinvsSpray-Dried Porcine Plasma Supplementation on Growth Performance, Metabolism and Immune Response of Weanling Piglets

Abstract: A total of 160 weaned pigs (PIC 327×1050, 7.35±0.50 kg body weight) were randomly assigned to four dietary treatments: i) control, a basal diet; ii) spray-dried porcine plasma (SDPP) diet, basal diet containing 4% SDPP; iii) SDPP plus yeast-deprived protein (YP) diet, basal diet containing 2% SDPP and 2% YP; and iv) YP diet, basal diet containing 4% YP. During the first week, average daily feed intake in piglets fed SDPP diet was markedly higher than piglets fed basal diet (+10%, P<0.05) and YP diet (+12%, P<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
4
3
1
Order By: Relevance
“…This difference was due to the performance variables, which demonstrates synergy between plasma and soy protein concentrate. These results are consistent with those reported by Hu et al (2014), who obtained higher final weight in the animals receiving a diet containing both soy protein concentrate and plasma. According to Coffey and Cromwell (1995), the best performance results are obtained with the use of plasma when the swine are raised in environments with a high pathogenic load.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This difference was due to the performance variables, which demonstrates synergy between plasma and soy protein concentrate. These results are consistent with those reported by Hu et al (2014), who obtained higher final weight in the animals receiving a diet containing both soy protein concentrate and plasma. According to Coffey and Cromwell (1995), the best performance results are obtained with the use of plasma when the swine are raised in environments with a high pathogenic load.…”
Section: Resultssupporting
confidence: 83%
“…These authors observed that the presence of 2 or 4% BP promoted increased feed intake and weight gain, with no difference observed in the feed conversion of piglets between 21 and 35 days of age. These results are consistent with those reported by Hu et al (2014), such that diets containing both soy protein concentrate and plasma had a greater beneficial effect on daily weight gain and average daily intake during the first post-weaning week. Ermer et al (1994) and Van Dijk et al (2001) suggested that the optimal performance during this period is related to the increased palatability of the feed with the inclusion of plasma and its health-promoting effects.…”
Section: Resultssupporting
confidence: 83%
“…Still, according to Boyer et al (2015), the inclusion of 5% SDP increased immunological responses in early-life pigs. The same was observed by Hu et al (2016), which related benefits for growth performance of piglets with inclusion of 2% SDP combined with 2% of yeast-deprived protein.…”
Section: Experiments 3: Blood Evaluationsupporting
confidence: 68%
“…The high quality of YH makes it a possible substitute for SDPP. However, few studies (Hu et al, 2014) have demonstrated whether YH can lower stress on piglets as SDPP does. Therefore, the purpose of this study was to investigate the effects of full or semi-replaced SDPP with YH in creep feed on related indices of weaned piglets, including feed intake, serum biochemical indexes, immune function, and intestinal structure.…”
Section: Introductionmentioning
confidence: 99%